A Comparison of Zooplankton Assemblages in a Coastal Upwelling and Offshore Station in East Sulu Sea - Acabado, Cristy S; Campos, Wilfredo L.; Noblezada, Mary Mar P.; Estremadura, DM G. (Science Diliman: A Journal of Pure and Applied Sciences, 2011)
Partially enclosed marine basins often display characteristic pelagic faunal compositions reflecting their distinctive hydrographic conditions. Seasonal upwelling along the northern coast of the Zamboanga Peninsula in East Sulu Sea results to the high fisheries production in the area likely by enhancing local plankton abundance. Zooplankton in this area were investigated during the Joint PhilEx oceanographic cruise on board the R/V Melville in December 2007. Data on the abundance and vertical distribution of major groups of zooplankton were analyzed and compared between two sets of MOCNESS samples collected from a coastal upwelling station and the other from an offshore station. Eighty four (84) zooplankton taxa belonging to 20 major groups were identified in the coastal station, while ninety five (95) taxa under 28 major groups were found in the offshore station. The total zooplankton density was much higher in the coastal station (98.9 ind./m 3 ) than in the offshore station (47.5 ind./m 3 ). Copepods dominated in both stations, comprising up to 70% of the total zooplankton. No distinct variation in the abundance, composition and distribution of zooplankton with depth was observed except in 150 – 200 m depth stratum in the coastal station wherein a dramatic increase in the abundance of copepods, ostracods and chaetognaths was noted. In the offshore station, the crustaceans also showed a drastic increase in abundance in the 50 – 100 m depths. These appear to be related to the thermocline in both stations, where typically higher upper layer primary productivity can support dense communities of zooplankton.
Keywords: upwelling; thermocline; zooplankton; Sulu Sea